CITRAAN DALAM ANTOLOGI “PUISI-PUISI CINTA” KARYA W.S. RENDRA - Bela Margareta; Chairil Effendy; Martono Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe background of this study is analyzing and decriminalizing Citraan in the anthology of “Puisi-puisi Cinta” by W.S. Rendra. The imagery includes visual imagery, auditory imagery, touch imagery, taste imagery, olfactory imagery, motion imagery, and feeling imagery. The purpose of this study is to be able to describe Citraan in the Anthology of “Puisi-puisi Cinta” by W.S. Rendra. This research uses descriptive methods and qualitative research forms. The approach used in this research is structural. The data in this study is sourced from the Anthology of “Puisi-puisi C inta”by W.S. Rendra. Based on the results of analysis on poetry there are images of vision, auditory imagery, image of touch, imagery of smell, imagery of motion, and image of feelings in it then this study has a link to the learning of Indonesian Language and Literature class X odd semester curriculum 2013 refers to Basic Competence 3.17 and 4.17. The results of this study are expected to be useful for many circles, especially for teachers, learners, and for further researchers.Keywords: Imagery, Implementation, Poem